From disease- to people-centred pandemic management: organized communities, community-oriented primary care and health information systems - Christine Leyns; Sara Willems; Richard A. Powell; Vivian Camacho; Ricardo Fabrega; Jan De Maeseneer; Salman Rawaf; Punam Mangtani; Austen El-Osta (BMC, 2023)
Abstract Background The COVID-19 pandemic exposed the health equity gap between and within countries. Western countries were the first to receive vaccines and mortality was higher among socially deprived, minority and indigenous populations. Surprisingly, many sub-Saharan countries reported low excess mortalities. These countries share experiences with community organization and participation in health. The aim of this article was to analyse if and how this central role of people can promote a successful pandemic response. Methods This analysis was partly based on local and national experiences shared during an international and Latin American conference on person-and people-centred care in 2021. Additionally, excess mortality data and pandemic control-relevant data, as well as literature on the pandemic response of countries with an unexpected low excess mortality were consulted. Results Togo, Mongolia, Thailand and Kenya had a seven times lower mean excess mortality for 2020 and 2021 than the United States of America. More successful pandemic responses were observed in settings with experience in managing epidemics like Ebola and HIV, well-established community networks, a national philosophy of mutual aid, financial government assistance, more human resources for primary care and paid community health workers. Discussion Since trust in authorities and health needs vary greatly, local strategies are needed to complement national and international pandemic responses. Three key levers were identified to promote locally-tailored pandemic management: well-organized communities, community-oriented primary care, and health information systems. An organized community structure stems from a shared ethical understanding of humanity as being interconnected with each other and the environment. This structure facilitates mutual aid and participation in decision making. Community-oriented primary care includes attention for collective community health and ways to improve health from its roots. A health information system supports collective health and health equity analysis by presenting health needs stratified for social deprivation, ethnicity, and community circumstances. Conclusions The difference in excess mortality between countries during the COVID-19 pandemic and various country experiences demonstrate the potential of the levers in promoting a more just and effective health emergency response. These same levers and strategies can promote more inclusive and socially just health systems.